2006
DOI: 10.1002/bmc.589
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of zolpidem in human plasma by liquid chromatography–electrospray ionization tandem mass spectrometry

Abstract: A simple and robust method for quantification of zolpidem in human plasma has been established using liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI MS/MS). Es-citalopram was used as an internal standard. Zolpidem and internal standard in plasma sample were extracted using solid-phase extraction cartridges (Oasis HLB, 1 cm3/30 mg). The samples were injected into a C8 reversed-phase column and the mobile phase used was acetonitrile-ammonium acetate (pH 4.6; 10 mm) (80:20, v/v) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
1
9
0
1
Order By: Relevance
“…The MS/MS fragmentation of zolpidem and its most abundant in vitro mono‐oxygenated metabolite (M1) are rationalized in Figure 3. Major peaks in both spectra related to neutral losses from the amide containing side‐chain, which is consistent with the previously reported MS/MS spectra of zolpidem 10. The same neutral MS/MS losses were also identified in the spectra of the carboxy (M5) and in two of the remaining mono‐oxygenated metabolites (M2 and M3), suggesting that each of these oxidations occurred on the aromatic rings rather than the amide‐containing side chain.…”
Section: Resultssupporting
confidence: 89%
“…The MS/MS fragmentation of zolpidem and its most abundant in vitro mono‐oxygenated metabolite (M1) are rationalized in Figure 3. Major peaks in both spectra related to neutral losses from the amide containing side‐chain, which is consistent with the previously reported MS/MS spectra of zolpidem 10. The same neutral MS/MS losses were also identified in the spectra of the carboxy (M5) and in two of the remaining mono‐oxygenated metabolites (M2 and M3), suggesting that each of these oxidations occurred on the aromatic rings rather than the amide‐containing side chain.…”
Section: Resultssupporting
confidence: 89%
“…samples. Bhatt et al (2006) observed no instability of zolpidem in samples stored for 60 days at 70°C; mean percent changes <13% were estimated from plasma stored at room temperature and from processed samples in the autosampler (5°C) after 6 and 24 hours, respectively. A comprehensive overview on the stability of antidepressants, neuroleptics, antiepileptics and cardiovascular drugs is given by Peters (2007).…”
Section: Stability Of Particular Drugs and Potential Artefacts In Blomentioning
confidence: 99%
“…The literature search revealed several reported analytical approaches for the determination of zolpidem in biological materials including liquid chromatography with fluorescence [4][5][6][7], ultraviolet [8,9] or mass detection [10][11][12][13], gas chromatography [14][15][16][17] and capillary electrophoresis [18]. Determination of zolpidem tartrate in the presence of zolpacid and dimethylamine was performed by HPTLC and HPLC methods [19].…”
Section: Introductionmentioning
confidence: 99%